2019
DOI: 10.37080/nmj.69
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care Practices among Hypertensive Patients of all Aged Group in Tsum- Nubri Rural Municipality of Gorkha District

Abstract: Introduction: Hypertension is now becoming an increasingly important cause of morbidity and mortality in developing countries which leads to a major public health problem. It is necessary for an assessment of an individual’s hypertension self-care behavior and its associated factors in order to provide clinicians about important information regarding how to better control hypertension. Thus, the objective of this study was to assess the self-care practices among hypertensive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…In most parts of the Himalayan region, walking on foot is the preferrable mode of transportation due to off road condition. 15 The study concluded that, 18.3% of the respondents had insufficient money for the treatment, due to which 9.6 % of the respondents visited traditional health services. Similar type of study conducted in Mahottari district concluded that Modern, Alternative and Self medications were common in the Rajbanshi community.…”
Section: Resultsmentioning
confidence: 98%
“…In most parts of the Himalayan region, walking on foot is the preferrable mode of transportation due to off road condition. 15 The study concluded that, 18.3% of the respondents had insufficient money for the treatment, due to which 9.6 % of the respondents visited traditional health services. Similar type of study conducted in Mahottari district concluded that Modern, Alternative and Self medications were common in the Rajbanshi community.…”
Section: Resultsmentioning
confidence: 98%
“…Still, 13.8% of participants followed traditional treatment, which was similar to other studies conducted in Manang, Bharatpur, Nepal and in rural area of eastern Uttar Pradesh, India. 9,10,15 The study showed that the majority of the participants preferred government health facility (65.1%) for the treatment, and still 9.2% preferred Dhami/Jhakri. The high preference for government health facilities might be due to affordable services in government facilities.…”
Section: Discussionmentioning
confidence: 94%